PEREMPUAN DALAM PERSPEKTIF ALQUR’AN, STUDI TAFSIR ATH-THABARI - Mohamad Mualim (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
This research discusses the views of the Alquran towards women, and the various important roles that are embedded in women in social life, from a small scale in the form of a family, as well as on a large scale as the leader of a group, groups and even the leader of a nation. So phenomenal is the role of this woman that the Alquran mentions many verses in the Alquran. This article will also discuss several types of women from the perspective of the Koran, as well as some of the views of scholars of interpretation of the role of women from time to time.